Pedestrian temporal gap acceptance behavior at unsignalized intersections in Kanpur, India. (October 2020) - Vasudevan, Vinod; Mehta, Mayur; Dutta, Bhupali
Highlights: Pedestrians face high risk while crossing unsignalized intersections. Temporal gap acceptance behavior of pedestrians at unsignalized intersection are studied. Used videography and manual observations for data collections. The pedestrians accept rolling gaps to cross unsignalized intersections, reducing the size of the critical gap. Peer pedestrians and approaching vehicle composition have a strong effect on pedestrian crossing behavior. Abstract: Vehicle heterogeneity, lack of lane discipline, lack of infrastructure facilities, and weak enforcement of traffic rules are all characteristics of Indian traffic. These characteristics make Indian roads difficult for non-motorized road users, especially pedestrians. Most intersections in urban areas in India are unsignalized, which results in complex interactions between pedestrians and motorists. This study aims to understand pedestrian gap acceptance behavior at unsignalized intersections in India under heterogeneous traffic conditions. Pedestrian data were collected from six unsignalized intersections in the city of Kanpur. The critical gap was estimated using Wu's (2006) macroscopic model, and then the effects of several variables on the critical gap were studied. A discrete choice model (binary logit model) was developed to understand the choice of accepted and rejected vehicular gaps depending on traffic, road, and peer pedestrian characteristics. The mean critical headway was 3.76 s using Wu's model. The behavioral analysis revealed that pedestrians accept rolling gaps to cross unsignalized intersections, resulting in a reduction of the size of the critical gap. The adoption of rolling gap behavior can be attributed to the unyielding behavior of motorists, which forces pedestrians to accept short vehicular gaps in the traffic stream.